Impacts of Infrastructure Developments on Ecosystem Services Potential in Istanbul - Menteşe, Emin Yahya; Tezer, Azime (Frontiers in Environmental Science, 2021)
Istanbul has been subject to drastic spatial changes in the last decade due to major investments in the northern section of the city. The primary purpose of the research was to interpret the ecological outcomes of spatial use changes due to such urban development activities and enhance the environmental impact assessment process by adopting an analytical and holistic approach. The approach used in the analysis is based on a model called “matrix model” developed specifically to estimate ecosystem services (ES) capacity of a given area depending on the spatial use types. With the use of this method, one can estimate how spatial use influences ES capacity in positive or negative ways, which ES type is affected most, and which part of the spatial change causes most impact on ecological assets. The methodology is applied for three different investment projects in Istanbul, respectively: North Marmara Motorway (NMM), Istanbul Airport, and Canal Istanbul. While the first two have been mostly completed, the third is in the planning phase. Corine Land Cover datasets for 2012 and 2018 are used as basis datasets within the methodology, and spatial plans of Canal Istanbul are used for future projections. Based on these datasets, ES capacity analysis is carried out for each year for the area of investment, and estimation results are compared. The analysis results indicate that these investments have caused and will cause severe ES losses as expected. The outputs prove that the “matrix model” can be used to evaluate ecological impacts in a straightforward, efficient, and inclusive way for evaluating spatial changes. The authors suggest that environmental impact assessments for such major investments must represent a comprehensive outlook based on more simplistic but yet informative approaches that highlight the potential losses of not only ecological assets but also their functions and benefits. In this context, it is strongly recommended that there is a paradigm shift in the understanding of the “environmental impact” in a direction where environment is not acted upon as a solid, rigid, and stable “land cover” but instead a living organism that produces benefits and services for the whole components of the ecosystem on earth, including humankind.